FEA Modelling of the Aluminium Alloy Graphene-based Composite Plate for the Launch Vehicle External Fuel Tank Structural Application (London Journal of Engineering Research, 2024)
The primary aim of this research is to investigate the structural uses of an aluminium alloy with a composite plate made of graphene in launch vehicle fuel tanks. To evaluate the viability and performance of the composite plate in this application, finite element analysis (FEA) modelling is used. The study aims to analyse the composite plate’s mechanical behaviour, thermal characteristics, and structural integrity under various loading scenarios, such as mechanical and thermal loads, stress, and strain. The outcomes of the FEA model are compared with the materials currently used in the external fuel tanks of launch vehicles. A cost analysis of the production process is also carried out to determine whether using the graphene-based composite plate is economically feasible. The study intends to provide light on the benefits, difficulties, and constraints related to the structural components of launch vehicle fuel tanks made of graphene-based composites. The results of this study have the potential to advance the discipline of aeronautical engineering and establish the framework for upcoming advances in materials science and design optimisation for launch vehicle applications.
Keywords: pirate attacks; risk analysis; K-means clustering; Autoencoder; EWM-TOPSIS; Compressive Strength; tensile strength; mechanical properties; compressed earth blocks (CEBs); eggshell waste; lime; Finite Element Analysis (FEA); Carbon Nanotubes (CNT); Liquid Oxygen (LOX); Liquid Hydrogen (LH2); External Fuel Tank (EFT).